Práticas gerenciais para hospital público universitário com base nos critérios de excelência da Fundação Nacional da Qualidade - Souza, Antão Tadeu de (2011)
This research aims to analyze and suggest management practices for a public university hospital, based on the requirements of the Standards of Excellence National Quality Foundation (FNQ), because they allow you to do a reading in a systematic way of all processes and practices of an institution essential to the process of organizational management. The method of research, this study is descriptive, mainly qualitative, their approach was based on analysis of management practices at a Public Hospital Federal University of Rio Grande do Sul The study sought to identify and interpret the requirements of Criteria for Excellence in literature and his approach in the management practices developed in the organization studied. The execution took place by applying the technique of search "Unstructured Observation". Based on the study, it is suggested that learning can be understood as practices of process improvement in hospitals, whose leaders have a critical role in its implementation may occur through review meetings, preparation or review of Strategic Planning. Finally, it is suggested that future research be undertaken with a view to developing an array of indicators that allows control and monitoring of results of systemic processes of this type of institution.